Atividade in vitro do (-)-mirtenol sobre fatores de virulência de candida albicans isoladas da cavidade oral - Soares, Camila Mendes (2024)
Candida albicans is a polymorphic yeast found in different anatomical sites of the human body, such as the oral cavity, gastrointestinal tract, and vaginal mucosa. This species is the most virulent and prevalent in various cases of candidiasis, such as oral candidiasis. However, conditions like immunosuppression, combined with the virulence factors of the species, facilitate the establishment and maintenance of the infection. Several studies focus on obtaining bioactive compounds with antifungal action, but few are aimed at targeting virulence factors. The present study aims to evaluate the action of (-)-myrtenol on the virulence factors of Candida albicans. Fourteen strains of C. albicans were used, 13 of which were collected from the oral mucosa of patients with oral candidiasis, and one reference strain (ATCC 90028). The virulence factors investigated were morphogenesis, lipase production, and biofilm formation. All assays were performed in the absence and presence of (-)-myrtenol, using a minimum inhibitory concentration (MIC) of 256 μg/mL determined by the microdilution technique in 96-well microplates. In all evaluated conditions, the compound was found to interfere with the expression of virulence factors: delay in germ tube formation (52% ± 10% vs. 28% ± 15%), reduction in filamentation capacity (3.10 ± 0.46 vs. 2.58 ± 0.64) in liquid and solid media, and hyphal length (92.09 ± 21.34 vs. 77.42 ± 17.56), as well as biofilm formation (0.18 ± 0.13 vs. 0.10 ± 0.10) for most strains. (-)-myrtenol also prevented the production and secretion of lipases. This was the first study to evaluate the action of (-)-myrtenol on the virulence factors of oral clinical isolates of Candida albicans, showing a significant reduction in germ tube formation and filamentation in the morphogenesis assays and, for most isolates, a reduction in biofilm formation and lipase secretion. Therefore, it is possible to highlight the potential of this compound as a therapeutic resource in inhibiting the development of oral candidiasis.